Are the Lives of Animals Well-spent in Laboratory Science Research? A Study of Orthopaedic Animal Studies in Turkey. Issue 9 (September 2020) - Öztürk, Alper; Ersan, Önder
Abstract: Background: As in all fields of medicine, animal studies are widely performed in orthopaedics and have increased in number over time. However, it is not clear to what extent these studies provide a basis for future research or advancements in clinical science. Concerns about the reliability and translational ability of animal studies have been reported, and major orthopaedic journals and organizations are encouraging the reduction of unnecessary experiments on animals. Question/purposes: (1) What proportion of animal studies conducted for orthopaedic research in Turkey were never published? And of those that were published, how long did it take to publish? (2) What proportion of those studies were published in journals with an Impact Factor of 2 or more? (3) What proportion of those published papers were never cited or cited only once? (4) What was the contribution to science of an animal euthanized for orthopaedic research in Turkey? Methods: We reviewed all oral and poster presentations at the Turkish National Congress of Orthopaedics and Traumatology from 2009 to 2017 (retrieved from the archives of Acta Orthopaedica et Traumatologica Turcica ), as well as all postgraduate theses in orthopaedics from 1991 to 2017 (retrieved from the archives of the National Thesis Center of the Council of Higher Education) to identify all orthopaedic studies that involved animals. We searched the keywords "animal studies, " "experimental studies, " and "orthopaedics" in these archives. We defined animal research as orthopaedic studies based on animal models. From this search and using that definition, 252 studies were identified. Of those, 4% (9) were excluded as they were thesis studies with no abstract in the archives. Thus, a total of 243 animal studies performed in Turkey were included for analysis in this retrospective study. The abstracts of these studies were examined to determine the study model (such as bone fracture models, tendon healing models, cartilage models) and number of euthanized animals. Between 1991 and 2017, 9412 vertebrate animals were euthanized for these studies. We searched PubMed, Google Scholar, ResearchGate, and ORCID to determine whether these papers were subsequently published, in which journal, and how long after the initial presentation publication occurred. The Web of Science 2019 database was used to determine the Impact Factor of the journals, the total citation count of each study, and the mean annual citation for each study (citations per year). For purposes of this analysis, we divided journals into those with an Impact Factor of 2 or more, 4 or more, and those with an Impact Factor below 2. The mean annual citation per euthanized animal (citations per animal per year) was calculated to determine the contribution of a euthanized animal to science. Results: A total of 42% (101 of 243) of the animal studies in Turkey were never published. For all published studies, the mean time to publication was 2.2 ± 2.6 years (95% CI 1.7 to 2.6). The proportion of studies published in orthopaedic journals with an Impact Factor of 2 or more was 14% (34 of 243). Among the 142 published papers, 38% (54) were either never cited or were cited only once, and the mean citations per year was 1.1 ± 1.7 (95% CI 0.7 to 1.3). The mean citations per animal/year among the 142 published studies was 0.03 ± 0.04 (95% CI 0.02 to 0.04). Conclusion: In the 243 theses and national congress presentations, 9412 animals were euthanized. Based on the low percentage of papers using animals that were euthanized and the very low proportion of studies published in higher-Impact Factor journals or garnering more than a single citation, in aggregate, little seems to have been gained from the loss of animal life. Future studies should try to replicate or refute our results in other countries. Clinical Relevance: Orthopaedic researchers should try to reduce their use of unnecessary animal studies, for example, by reporting on the use of the "3Rs" (replacement, reduction, and refinement) in the development of an animal study design, as well as through following universal guidelines so that a study might have a clinical impact. Researchers should not conduct an animal study until they are convinced that the expected results are quite likely to deliver substantial benefit to people or to advance science in a meaningful way; although this seems intuitive, our results suggest that this may not be taking place. Ethics committees in Turkey should consider more detailed questioning before approving animal studies. If our results are replicated elsewhere, then a broader look at how these approvals are conducted should be performed.